The State of Labor-Management Relations, 1958-1959 - Goldberg, Arthur (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1959)
SommaireAfter explaining Sidney Hillman's contribution to labor philosophy and to improved labor-management relations, the author draws a vivid picture of the present state of labor-management relations. Hillman believed in the mutuality of interests between both sides, but there was no question of surrendering to Management. We are a long way from a universal achievement of the type of labor-management relations symbolysed by the Sidney Hillman's tradition. Union organization meets with resistance; all parties toughen their attitudes and restrict their meetings to those around the bargaining table. To bridge the gap and introduce more talks on basic issues between sides, a Labor-Management Assembly is proposed.